A novel andrographolide derivative AL‐1 exerts its cytotoxicity on K562 cells through a ROS‐dependent mechanism. Issue 1 (11th December 2012) - Zhu, Yong‐Yang; Yu, Guangchuang; Zhang, Ye; Xu, Zheng; Wang, Yu‐Qiang; Yan, Guang‐Rong; He, Qing‐Yu
<x xml:space="preserve">Abstract</x> Andrographolide‐lipoic acid conjugate (AL‐1) is a new in‐house synthesized chemical entity, which was derived by covalently linking andrographolide with lipoic acid. However, its anti‐cancer effect and cytotoxic mechanism remains unknown. In this study, we found that AL‐1 could significantly inhibit cell viability of human leukemia K562 cells by inducing G2/M arrest and apoptosis in a dose‐dependent manner. Thirty‐one AL‐1‐regulated protein alterations were identified by proteomics analysis. Gene ontology and ingenuity pathway analysis revealed that a cluster of proteins of oxidative redox state and apoptotic cell death‐related proteins, such as PRDX2, PRDX3, PRDX6, TXNRD1, and GLRX3, were regulated by AL‐1. Functional studies confirmed that AL‐1 induced apoptosis of K562 cells through a ROS‐dependent mechanism, and anti‐oxidant, N‐acetyl‐l‐cysteine, could completely block AL‐1‐induced cytotoxicity, implicating that ROS generation played a vital role in AL‐1 cytotoxicity. Accumulated ROS resulted in oxidative DNA damage and subsequent G2/M arrest and mitochondrial‐mediated apoptosis. The current work reveals that a novel andrographolide derivative AL‐1 exerts its anticancer cytotoxicity through a ROS‐dependent DNA damage and mitochondrial‐mediated apoptosis mechanism.